Study in Agroindustry of Salted Egg: Length of Salting Process and Marketing Reach Aspects - Wulan Sumekar; Ahmad Ni'matullah Al-Baarri (Journal of Applied Food Technology, 2020)
Homemade salted egg production leading to one of agro-industry products has been identified as profitable, yet processing technology of salting needs to be improved. The objective of the study was to analyze the length of salting application of salted eggs, marketing reach, and association between the lengths of salting application with marketing reach. Forty respondents determined by purposive random sampling was carried out on agro-industry center of salted eggs in Brebes, Central Java. The primary data (length of salting and marketing reach) were collected by interview using questionnaire and observation. The levels of NaCl of salted eggs were measured by Argentometri Mohr method. The secondary data were collected by recording relevant documents. Data of length of salting and marketing reach were analyzed descriptively. Relationship between the length of salting and the marketing reach of salted eggs were analyzed using contingency tables with the X2 test. The result showed that all respondents applied length of salting with time duration of salting varied from 12 to 30 days, during which period 52.5% respondents did the salting in >14-18 days. The salinity was still relatively higher than that of recommended by the Indonesian Industry Standard (SNI), which is 2.0%. The respondents also functioned as marketing components; such as consumers, retailers-consumers, and collectors - retailers - consumers with the percentage of 52.5, 35, and 12.5%, respectively. As conclusion, the length of salting technology application might influenced marketing reach and the length of salting technology application mostly could only reach the short marketing.